1990
DOI: 10.1021/bc00002a010
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity of oligonucleotide-poly(L-lysine) conjugates: mechanism of cell uptake

Abstract: We have previously shown that antisense oligomers linked to poly(L-lysine) (PLL) exhibit antiviral properties against vesicular stomatitis virus (VSV) at concentrations lower than 1 microM. The conjugation to PLL provides an interesting alternative to natural or neutral oligomers to increase the biological effects of antisense oligomers. The internalization pathway of oligomer-PLL conjugates as compared to unconjugated oligomers has been studied in L929 cells. In parallel to their enhanced antiviral activity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(78 citation statements)
references
References 21 publications
1
77
0
Order By: Relevance
“…These results suggest the existence of low-affinity/ high-occupancy sites for 4Rh on CHO cells reminiscent of a nonspecific uptake process. Poly(L-lysine) associates with the negatively charged surface of mammalian cells and is internalized by a process termed nonspecific adsorptive endocytosis (23,25,36). Interestingly, members of the integrin family of cell adhesion molecules-particularly a3913, a5131, and a691 could serve as a transitory class of cell surface receptors for CTS domains (37).…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest the existence of low-affinity/ high-occupancy sites for 4Rh on CHO cells reminiscent of a nonspecific uptake process. Poly(L-lysine) associates with the negatively charged surface of mammalian cells and is internalized by a process termed nonspecific adsorptive endocytosis (23,25,36). Interestingly, members of the integrin family of cell adhesion molecules-particularly a3913, a5131, and a691 could serve as a transitory class of cell surface receptors for CTS domains (37).…”
Section: Resultsmentioning
confidence: 99%
“…These include introduction of a lipophilic dodecanol chain, 49 5Ј-cholesterol, 50 and poly-l-lysine. 51 However, the conjugation of certain lipophilic groups to the ODN backbone may result in increased cell membrane association without increasing the delivery of ODN to the site of target mRNA. 52 ODN may be loaded into liposomal vesicles, [53][54][55] or associated with cationic liposomes, 48 although not nanoparticles 56 or polyethylenimine.…”
Section: Methods Of Enhancing Cellular Odn Uptakementioning
confidence: 99%
“…Cholesterol has been placed on the end of the molecule (Letsinger et al, 1989;Boutorin et al, 1989) while another modification has included acridine for intercalation at one end of the oligo and dodecanol at the other end (Saison-Behmoaras et al, 1991). Alternatives for delivering the oligodeoxynucleotides have included liposomes (Yeoman et al, 1992;Thiery and Dritschilo, 19921, absorption on polyalkylcyanoacrylate nanoparticles (Chavany et al, 1992) and absorption on poly-L-lysine (Lemaitre et aE., 1987;Leonetti et al, 1990). For RNA injections, it has been shown that capped in vitro transcribed RNA is more stable than uncapped RNA when injected into the cytoplasm (Bevilacqua and Erickson, 1988).…”
Section: Chemistry Of Antisense Reagentsmentioning
confidence: 99%